Effects of blood flow restriction on mechanical properties of the rectus femoris muscle at rest - Jarosz, Jakub; Gaweł, Dawid; Krzysztofik, Michal; Zając, Adam; Tsoukos, Athanasios; Bogdanis, Gregory C.; Wilk, Michal (Frontiers in Physiology, 2023)
This study examined the effects of blood flow restriction (BFR) and reperfusion on the mechanical properties of the rectus femoris muscle at rest (frequency and stiffness). Fourteen trained men (body weight = 81.0 ± 10.3 kg; BMI = 25 ± 3.0 m/kg 2 ; height = 181 ± 4 cm; training experience = 6.0 ± 2.2 years) participated in an experimental session involving their dominant (BFR) and non-dominant leg (control). Muscle mechanical properties were measured using Myoton's accelerometer at the midpoint of the rectus femoris muscle at five time points. In the BFR leg, an 80% arterial occlusion pressure was applied by a cuff for 5 minutes. No cuff was applied in the control leg. Femoral Myoton measurements were taken from both legs 2 and 4 minutes after the start of BRF as well as 30 s and 2 min after the end of the occlusion period. The two-way ANOVA revealed a statistically significant interaction effect for stiffness and frequency (p<0.001; η 2 >0.67). The post-hoc analysis showed that both stiffness and frequency increased during BFR compared with rest and then dropped to the resting levels post BFR period. Also, stiffness and frequency were higher than control only during the BFR period, and similar during rest and post BFR. These results indicate that the application of BFR at rest leads to significant changes in mechanical properties of the rectus femoris muscle.